Educational and professional background and success in the labor market: the case of Portuguese immigrants in the Netherlands - Lopes, Silvana Fernandes [UNESP] (My University, 2012)
The aim of this paper is to describe the relationship between educational and professional occupation trajectories of Portuguese immigrants in The Netherlands. To this end, the sample used comprises Portuguese immigrants that arrived in The Netherlands in two periods which represent the highest influx of immigrants: around the years 1966 and 2002. The analysis of the data shows a strong relationship between the level of professional education and the level of professional occupation. Furthermore, some exceptions to the generalizations found show that in service training may lead to an improvement of the possibilities to ascend regarding the level of professional occupation.

Cet article se propose de décrire la relation entre les trajectoires de l ́éducation et des activités professionnelles des immigrants portugais aux Pays-Bas. À cette fin, on a utilisé un échantillon d'immigrants portugais arrivés aux Pays-Bas en deux périodes qui représentent les plus grands afflux, aux alentours de 1966 et de 2002. L'analyse des données montre une relation forte entre le niveau de scolarisation et de professionalisation et le niveau du travail. En outre, les exceptions rencontrées contribuent à démontrer que la formation en cours d'emploi peut augmenter les chances d'évolution professionnelle.

O objetivo deste artigo é descrever a relação entre as tragetórias de educação e de ocupação profissional dos imigrantes portugueses na Holanda. Para tal, foi utilizada uma amostra constituída por portugueses que chegaram à Holanda nos dois períodos que representam o maior fluxo de imigrantes: por volta dos anos 1966 e 2002. A análise dos dados mostra uma forte relação entre o nível de formação educacional e profissional e o de ocupação laboral. Além disso, as exceções encontradas contribuem para demonstrar que a formação em serviço pode aumentar as possibilidades de ascensão no que respeita à ocupação profissional.
Formação educacional e profissional e sucesso no mercado de trabalho: o caso dos imigrantes portugueses na Holanda
Parcours scolaire et professionnel et la réussite sur le marché du travail: le cas des immigrants portugais aux Pays-Bas